Drivers of variation in the population dynamics of bighorn sheep. Issue 7 (22nd July 2021) - Paterson, J. Terrill; Proffitt, Kelly; Rotella, Jay; McWhirter, Douglas; Garrott, Robert
Abstract: Understanding how variation in vital rates interact to shape the trajectories of populations has long been understood to be a critical component of informed management and restoration efforts. However, an expanding body of work suggests that the expectations for population dynamics of ungulates may not be applicable to small, declining, or threatened populations. Populations of bighorn sheep ( Ovis canadensis ) suffered declines at the turn of the 20th century, and restoration efforts have been mixed such that many populations remain small and isolated. Here, we utilized survey data collected from 1983 to 2018 from 17 populations of bighorn sheep in Montana and Wyoming to estimate the parameters of a stage‐specific population model that we used to (1) characterize the spatial and temporal variation in key vital rates including whether populations were stable, increasing, or declining; (2) estimate the contributions of vital rates to variation in population growth rates; and (3) evaluate potential sources of variation in lamb survival. We found substantial variation in all vital rates both among years and populations, strong evidence for an overall decline in nine of the 17 populations, and clear evidence for multiple combinations of vital rates that resulted in positive population trajectories. The contribution of ewe survival and lamb survival to the total variation in population growth rates varied among populations; however, declines in ewe survival dominated transitions of population trajectories from stable or increasing to declining, whereas reversals of declining population trajectories were dominated by improved lamb survival. We found strong evidence for a diverse set of associations between lamb survival and environmental covariates related to growing season and winter severity. The estimated relationships predict that environmental drivers can cause important changes in lamb survival and provide suggestive evidence that the presence of Mycoplasma ovipneumoniae is not sufficient to prevent population growth. Although our work demonstrates that the trajectories of these populations of bighorn sheep are driven by a variety of processes, the diversity of relationships between vital rates and population growth rates also suggests that there are multiple pathways to manage for population recovery.